THE INFLUENCE OF SOCIAL COMMERCE AND E-PAYMENT SERVICES ON THE INCOME OF HALAL CULINARY MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN PANYABUNGAN SUB-DISTRICT - Rahmat, Paisal; Fitri, Meliani (Jurnal Al-Ijtimaiyyah, 2025)
This study aims to determine the effect of social commerce and e-payment services on the income of micro, small, and medium enterprises (MSMEs) in the culinary sector in Panyabungan District. The research method used is quantitative research. The population in this study consists of all culinary MSMEs that use social commerce and e-payment services, with a total population and sample size of 30 respondents. Data analysis techniques used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, f-tests, and coefficient of determination tests. Data processing tools in this study used SPSS 24 software. The results showed that the t-test on the social commerce service variable had a significance value of 0.003 < 0.05 and a t-value of 3.228 > the t-table value of 2.051, so Ha1 was accepted and H01 was rejected, meaning that social commerce services partially had a significant effect on the income of Micro, Small and Medium Enterprises in Mandailing Natal District. Then, the e-payment variable has a significance value of 0.028 < 0.05 and a t-value of 2.329 > the table t-value of 2.051. Thus, Ha2 is accepted and H02 is rejected, meaning that e-payment partially has a significant effect on the income of Micro, Small and Medium Enterprises in Mandailing Natal District. The f test results show that simultaneously or together, the social commerce and e-payment variables have a significant value of 0.000 < 0.05 and an f value of 10.969 > the f table value of 3.35, so Ha3 is accepted and H03 is rejected, meaning that social commerce services and e-payment simultaneously have a significant effect on the income of Micro, Small, and Medium Enterprises in Mandailing Natal District. Furthermore, the three main principles are in line with the practice of utilizing e-payment and social commerce services for halal culinary MSMEs in the Panyabungan sub-district. First, the principle of justice ('adl) emphasizes the fulfillment of the rights of all parties in a balanced manner. Second, the principle of transparency (al-amanah) requires the honest and trustworthy presentation of financial and non-financial information, as a form of accountability not only to fellow human beings but also to Allah. Third, the principle of benefit (maslahah) directs every business activity to provide broader benefits to society, not merely to pursue personal or group profits.